Perceptions towards service quality and impact on repatronage intention at Melaka River Cruise / Norasmah Mohd Nooh and Norsyafiqah Rosli - Mohd Nooh, Norasmah; Rosli, Norsyafiqah (Faculty of Business and Management, 2013)
This study focuses on “Perception towards Service Quality and Impact on Re patronage Intention” and objective is to identify whether the service quality used by Melaka River Cruise give impact towards customer re patronage intentions on Melaka River Cruise. This research is design to determine the suitability of service quality that can help to improve the service of Melaka River Cruise. The questionnaire was distributed randomly of 70 respondents. Based from useful 70 questionnaire analyzed, the service quality has relationship between customer re patronage intentions and Melaka River Cruise can improve their services to influence of the positive cruise experience towards customers.